2018
DOI: 10.1186/s12884-018-1971-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of logistic regression with machine learning methods for the prediction of fetal growth abnormalities: a retrospective cohort study

Abstract: BackgroundWhile there is increasing interest in identifying pregnancies at risk for adverse outcome, existing prediction models have not adequately assessed population-based risks, and have been based on conventional regression methods. The objective of the current study was to identify predictors of fetal growth abnormalities using logistic regression and machine learning methods, and compare diagnostic properties in a population-based sample of infants.MethodsData for 30,705 singleton infants born between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 32 publications
(30 reference statements)
3
61
0
2
Order By: Relevance
“…Our analyses revealed that ML algorithms and logistic regression models had comparable predictive accuracy when validated internally and externally. Our findings buttress current evidence from other published studies (28)(29)(30)(31)(32)(33) that already showed that the logistic regression and ML algorithms had comparable predictive accuracy in empirical clinical studies. A recently published systematic review found no evidence of the superior predictive performance of ML models over logistic regression models in clinical studies (32).…”
Section: Discussionsupporting
confidence: 90%
“…Our analyses revealed that ML algorithms and logistic regression models had comparable predictive accuracy when validated internally and externally. Our findings buttress current evidence from other published studies (28)(29)(30)(31)(32)(33) that already showed that the logistic regression and ML algorithms had comparable predictive accuracy in empirical clinical studies. A recently published systematic review found no evidence of the superior predictive performance of ML models over logistic regression models in clinical studies (32).…”
Section: Discussionsupporting
confidence: 90%
“…7 Early identification of pregnant women at risk for adverse maternal and perinatal outcomes during the prenatal period and timely provision of high-quality healthcare services have been reported to improve maternal and newborn survival. 9 Machine learning (hereafter denoted as 'ML') models are methodologies for developing algorithms that learn from existing data to make predictions on new data. 9 ML models have shown better predictive performance over the classical or conventional regression models, 10 and they can better handle a significant number of potential predictors.…”
Section: Introductionmentioning
confidence: 99%
“…9 Machine learning (hereafter denoted as 'ML') models are methodologies for developing algorithms that learn from existing data to make predictions on new data. 9 ML models have shown better predictive performance over the classical or conventional regression models, 10 and they can better handle a significant number of potential predictors. However, there is conflicting evidence of the performance of these models.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Rawat et al [64] implemented an ANN model using again 2-D US morphometric measurements from a total of 120 fetuses. Recently, Kuhle et al [65] compared different ML methods to predict fetal growth abnormalities in a cohort of more than 30,000 patients. However, the authors reported that the ML methods used did not offer any advantage over logistic regression in the prediction of fetal growth abnormalities.…”
Section: For Fetal Diagnosismentioning
confidence: 99%